Differential information and the small firm effect - Barry, Christopher B.; Brown, Stephen J. (Journal of Financial Economics, 1984)
We examine a model of market equilibrium in which there is less information available about some of the securities in the market than about others. We consider the model as a potential explanation of the well-known small firm anomaly. Using period of listing as a proxy for quantity of information, we find an association between period of listing and security returns that cannot be accounted for by firm size and which is not diminished by an elimination of January returns data from our sample. Thus, we observe a new empirical regularity in the data and refer to the regularity as the ‘period of listing’ effect.